In Vitro Activity of Ampicillin or Vancomycin Combined with Gentamicin or Streptomycin Against Enterococci - Harwick, Herbert J. (1973)
Minimum inhibitory and bactericidal concentrations of four antibiotics and their combinations were determined for 38 strains of enterococci by a microtitration tube dilution technique. The drugs were ampicillin, vancomycin, gentamicin, and streptomycin; the combinations were ampicillin-gentamicin, ampicillin-streptomycin, vancomycin-gentamicin, and vancomycin-streptomycin. At achievable serum concentrations, ampicillin alone killed 60% of strains, whereas combination with streptomycin increased this to 90% and with gentamicin to 100%. Vancomycin alone showed striking inhibitory activity, but very poor bactericidal activity at achievable concentrations. Combination with one of the aminoglycosides increased the bactericidal activity substantially. When combined with ampicillin, gentamicin was both more active and showed synergistic bactericidal activity significantly more often (P < 0.01) than streptomycin.